WHITEHEAD'S COSMOLOGY - PROCESS RELATIONAL PERSPECTIVE TO RELATIVITY AND QUANTUM MECHANICS. - Bansal, Deepak (Cosmos & History, 2018)
Whitehead believed that science and philosophy mutually criticize each other to provide imaginative material for their shaping the history of thought. In the early twentieth century, as a mathematician turned philosopher, he took up the task of challenging the emerging scientific theories of the time, such as relativity and quantum mechanics, and provided a radically novel cosmological scheme. He challenged the incoherence of the mechanistic materialistic scientific world with his visionary process-relational model, based on the ontology of organisms. Almost a century later, his challenges to science are as, or even more, valid. This paper explores Whitehead's struggle with relativity, reflects on his response to quantum mechanics, and reviews his tribute to God, based on his philosophical model, as an attempt to understand divergent perspectives on the nature of universe.